Pendampingan Implementasi Gerakan Literasi dalam Meningkatkan Minat Membaca pada Siswa SDN 1 Depok Kec. Darangdan Kab. Purwakarta - Ulan Nurmilah; Narkum Narkum; Dede Supendi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
One of the Community Service Lecture programs carried out by STAI Students. DR. KHEZ. Muttaqien Purakarta is a literacy movement to increase children's interest in reading in Depok Village, Darangdan District, Purwakarta Regency which focuses on students at SD Negeri 1 Depok. In this case, basically the results of observations, interviews and direct participation in the learning process resulted in the problem that from class I to class VI there were some students who were not yet fluent in reading in each class. This is due to low interest in reading, lack of teachers, and libraries that are less than optimal in use. So, this is what makes us carry out a literacy movement program with the activities of providing a mobile library, book review activities and literacy posts with the aim of providing literacy facilities and forming habits in children in order to increase interest in reading among students at SD Negeri 1 Depok in particular and generally for children from Depok Village. In implementing this program, qualitative methods and a Participatory Action Research (PAR) approach are used, all of which lead to a context of discovery, empowerment and change.